Abordagens e Ferramentas para o Ensino de Programação em Blocos para Crianças Autistas - SOFIA ROLIM BARBOSA (2024)
Block-based programming has proven to be a promising tool for the development of children with Autism Spectrum Disorder (ASD). Eight studieswere analyzed that investigated the use of different block programming tools, such as Scratch, OzoBlockly and Code.org, at different school levels. The results demonstrated the positive impact of block programming on the cognitive, social and emotional development of children with ASD, promoting skills such as computational thinking, problem solving, communication, collaboration and self-esteem. However, challenges such as difficulty understanding abstract concepts and behavioral problems have been identified, and strategies such as explicit instruction, use of visual materials, and personalization of teaching have been suggested to overcome them. This study contributes to the understanding of the potential of block programming for children with ASD and offers guidelines for its effective implementation in the educational context, with the aim of promoting more inclusive and equitable educational practices.